Strategy model of coastal women's economic empowerment (fisherman's wife) based on blue economy and local potential in kenjeran beach tourism location city of Surabaya - Nekky Rahmiyati; Titiek Rachmawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to find out the role coastal women in improving the economy of fishermen's families, the role of coastal women in implementing the blue economy, the right model of empowerment strategies for coastal women. The types of research are quantitative, the number of samples is 50 and the sampling technique is purposive sampling. This study uses SWOT analysis. The results of the SWOT analysis show that the main strategy produced is the SO strategy with the highest score of 3.9 in position 1, which is to use strength to seize and take advantage of opportunities as large as possible. The role of coastal women in using local potential on tourist beaches is still not optimal because KPPI members do not have the skills, in particular there is no innovation and there is no variety of products from fishermen's catches, and weak marketing strategies.